Discovery of somatic STAT5b mutations in large granular lymphocytic leukemia - Rajala, Hanna L. M. (American Society of Hematology, 2013)
Large granular lymphocytic (LGL) leukemia is characterized by clonal expansion of cytotoxic T cells or natural killer cells. Recently, somatic mutations in the signal transducer and activator of transcription 3 (STAT3) gene were discovered in 28% to 40% of LGL leukemia patients. By exome and transcriptome sequencing of 2 STAT3 mutation-negative LGL leukemia patients, we identified a recurrent, somatic missense mutation (Y665F) in the Src-like homology 2 domain of the STAT5b gene. Targeted amplicon sequencing of 211 LGL leukemia patients revealed 2 additional patients with STAT5b mutations (N642H), resulting in a total frequency of 2% (4 of 211) of STAT5b mutations across all patients. The Y665F and N642H mutant constructs increased the transcriptional activity of STAT5 and tyrosine (Y694) phosphorylation, which was also observed in patient samples. The clinical course of the disease in patients with the N642H mutation was aggressive and fatal, clearly different from typical LGL leukemia with a relatively favorable outcome. This is the first time somatic STAT5 mutations are discovered in human cancer and further emphasizes the role of STAT family genes in the pathogenesis of LGL leukemia.